2021
DOI: 10.1016/j.proci.2020.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flow field dynamics on soot evolution in an aero-engine model combustor

Abstract: Large-Eddy Simulation of a sooting aero-engine model combustor is analyzed by means of proper orthogonal decomposition (POD) to investigate the influence of flow field dynamics on soot evolution. Since classical POD fails to extract the low-frequency intermittent dynamics of scalars such as soot volume fraction, the recently-introduced multiresolution POD (MRPOD) is deployed to treat the LES results instead. MRPOD essentially provides additional dynamic rankings of energetic POD modes via bandpass filters cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 26 publications
5
21
0
Order By: Relevance
“…5a, φ3). A recent numerical study by Grader et al [45] found that this low-frequency alternation of the backflow velocity in the IRZ is mostly caused by fluctuations of the secondary air injection further downstream. So far unpublished results from the computations presented in [45] confirm the existence of an independent DHV structure, benefitting from the 3D character of simulations, and therefore support our interpretation.…”
Section: Spectral Analysis Using Podmentioning
confidence: 96%
“…5a, φ3). A recent numerical study by Grader et al [45] found that this low-frequency alternation of the backflow velocity in the IRZ is mostly caused by fluctuations of the secondary air injection further downstream. So far unpublished results from the computations presented in [45] confirm the existence of an independent DHV structure, benefitting from the 3D character of simulations, and therefore support our interpretation.…”
Section: Spectral Analysis Using Podmentioning
confidence: 96%
“…However, the local instantaneous measurement of flowfield features is quite challenging in sooting flames due to substantial interference from elastic scattering and spontaneous flame radiation. Due to the complexity in local measurements, only a limited number of studies report local correlations of soot and flow field parameters. In a narrow soot inception region in simple jet flames, a preferred velocity of 3 m/s and a strain rate of 700 s –1 were found most favorable for soot formation. , In a series of turbulent swirling flames, simultaneous soot-flow measurement reveals that soot is formed in the inner recirculation zone and partly transported to the high-velocity inflow region. However, these measurements have not systematically investigated the local mixing effects by measuring the local strain rates on SVF in their flames.…”
Section: Introductionmentioning
confidence: 91%
“…Time-averaged soot volume fraction fv fields in the DLR burner obtained from low repetition rate measurements [11] and LES are presented in Fig. 1.…”
Section: Variability Of Time-averaged Soot Fieldsmentioning
confidence: 99%
“…As an example, in the DLR model combustor [9], the presence of a precessing vortex core (PVC) affects the mixture in the primary combustion zone by interacting with the fuel injection. As a consequence, soot production, which strongly depends on the local conditions of the gas mixture, evolves intermittently in space and time [10][11][12]. In addition, the dynamics of secondary air jets, characterized by much longer times compared to the PVC, have an impact on the flow structure and, consequently, on soot production [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation